2020
DOI: 10.21203/rs.3.rs-79381/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental Exposure to DDT or DDE Alters Sympathetic Innervation of Brown Adipose in Adult Female Mice

Abstract: Background: Exposure to the bioaccumulative pesticide dichlorodiphenyltrichloroethane (DDT) and its metabolite dichlorodiphenyldichloroethylene (DDE) has been associated with increased risk of insulin resistance and obesity in humans and experimental animals. These effects appear to be mediated by reduced brown adipose tissue (BAT) thermogenesis, which is regulated by the sympathetic nervous system. Although the neurotoxicity of DDT is well-established, whether DDT alters sympathetic innervation of BAT is unkn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…However, a follow-up study by Warner et al, found significant association between DDT and higher BMI zscores among boys at 12 years of age (Warner et al, 2017), and a metaanalysis of 33 epidemiological studies found that prenatal levels of DDE and HCB was associated with higher BMI z-score among children (Stratakis et al, 2022). Also, animal studies, suggest that prenatal exposure to DDE and HCB alters metabolic markers in mice and rat offspring (Al-Obaidi et al, 2022;La Merrill et al, 2014;vonderEmbse et al, 2021). Follow-up analysis in our study population would be informative to whether associations can be found later in childhood or puberty.…”
Section: Discussionmentioning
confidence: 99%
“…However, a follow-up study by Warner et al, found significant association between DDT and higher BMI zscores among boys at 12 years of age (Warner et al, 2017), and a metaanalysis of 33 epidemiological studies found that prenatal levels of DDE and HCB was associated with higher BMI z-score among children (Stratakis et al, 2022). Also, animal studies, suggest that prenatal exposure to DDE and HCB alters metabolic markers in mice and rat offspring (Al-Obaidi et al, 2022;La Merrill et al, 2014;vonderEmbse et al, 2021). Follow-up analysis in our study population would be informative to whether associations can be found later in childhood or puberty.…”
Section: Discussionmentioning
confidence: 99%